(untitled) (Research, Society and Development, 2025)
Introduction: Obstetric violence is an issue that permeates maternal healthcare, and its impact is pronounced when considering the intersection with structural racism. Black women face unique and disproportionate challenges during the processes of pregnancy, childbirth, and postpartum, due to various factors, including implicit and explicit biases, lack of access to quality care, and socio-economic inequalities. Objective: This study aims to investigate the impact of racism on obstetric violence experienced by Black women. Methodology: This is an integrative review with a descriptive character of articles published in Portuguese selected from the BVS SciELO and Google Scholar databases. 16 articles were chosen through a search using the descriptors: Obstetric violence, Racism; Nursing, using the boolean operator AND as a tool for crossing the descriptors, with a review of articles published from 2019 to 2024. Results and Discussion: It has been found that obstetric violence against Black women involves episodes of physical, sexual, verbal, psychological, and institutional violence during labor, delivery, and postpartum. It also includes lack of information, racial discrimination, difficulty in accessing prenatal care, and rights violations, all contributing to the vulnerability of Black women. Conclusion: It is concluded that the impact of covert racism and obstetric violence on Black women reinforces the need for humanized care focused on women’s protagonism, with inclusive practices and the fight against rights violations.